Case Report: Transient myocardial thickening in a cat secondary to acute cholangiohepatitis - Kim, Byung-Jun; Park, Mi-Kyung; Song, Kun-Ho (Frontiers in Veterinary Science, 2026)
Transient myocardial thickening (TMT) has been reported mainly in young cats following systemic triggers such as anesthesia, surgery, acute stress, or infection; however, to the authors’ knowledge, TMT secondary to acute cholangiohepatitis has not been described. A 3-year-old, 5.8-kg castrated male Abyssinian was referred with acute cholangiohepatitis. Initial evaluation revealed increased hepatic enzymes and bilirubin, elevated cardiac troponin I (cTnI, 3.5 ng/mL), and mildly increased N-terminal pro-B-type natriuretic peptide (NT-proBNP, 102.6 pmol/L). On the day of discharge, despite improving hepatic indices, cTnI rose abruptly to 8.0 ng/mL and NT-proBNP exceeded 1,500 pmol/L. Echocardiography demonstrated septal thickening, left atrial enlargement, and systolic anterior motion of the mitral valve, consistent with TMT. Atenolol was added to the outpatient medical management for cholangiohepatitis, consisting of broad-spectrum antimicrobials, hepatoprotectants, and antiemetic/gastroprotective agents. Over the course of 84 days, five follow-up evaluations were performed, during which hepatic values normalized, cTnI and NT-proBNP returned to reference ranges, and myocardial dimensions and vertebral heart score normalized. Unlike most reports in which TMT is identified after congestive signs develop, this case was recognized earlier, on the basis of an abrupt biomarker surge during apparent clinical improvement.